One-dimensional Simulation Study of Intermediate Temperature Fuel Cell - Wang,Wenqian (2024)
In the past decade, there has been a major shift in automotive propulsion systems from fossil fuel vehicles to environmentally friendly, zero-emission transportation. This has made hydrogen-powered vehicles a hot topic. Volvo Group has launched a fuel cell truck to promote energy transition. A fuel cell consists of two electrodes (anode and cathode) and an electrolyte membrane inserted between them. A single fuel cell can produce a theoretical voltage of about 1.2 volts. Proton exchange membrane fuel cells (PEMFCs) are considered to be commercially promising fuel cells due to their high efficiency, low-temperature operation, high power density, fast start-up, and system robustness. However, in reality, the voltage output will drop due to various polarization losses. In order to effectively utilize fuel cells, mathematical models must be established to predict the system behaviour under different conditions such as load current, reaction gas pressure, temperature, and stack voltage through computer simulation during the design stage. Research shows that PEMFC faces some problems when operating below 80°C and above 120°C. Medium-temperature PEMFC can achieve a good balance. However, it is still unclear how changes in each parameter within the fuel cell will affect the output performance. This thesis combines previous research and attempts to explain the effects of different parameters on the polarization curve in the model. This work will provide direction for the calibration of more accurate fuel cell models.
Keywords: PEMFC; cell calibration; Modeling; GT-suite; Dynamic